Shocks and rural development policies: Any implications for migrants to return? - Manh Hung Do; Nguyen-Trung-Thanh; Thanh Tung Nguyen; Ulrike Grote (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2020)
This paper examines the factors affecting the decision of migrants to return home in rural areas and their length of stay in cities with a focus on shocks and rural development policies. We use the unique Thailand Vietnam Socio Economic Panel (TVSEP) data. Our results reveal that the decision to return is positively associated with demographic shocks and negatively associated with social shocks during the time migrants stay in the cities. Meanwhile, economic shocks positively influence migrants' staying period in the cities. Besides, migrants from poor communes with poverty reduction projects are more unlikely to return. This implies that current rural development policies in Vietnam with a goal of poverty reduction might not be attractive enough for migrants to return.
Keywords: J62; D13; O13; Q12; 330; Two-step Heckman selection; Shocks; Rural-urban migration; Migrants' behavior; Rural development